Intestinal Obstruction due to Colonic Lithobezoar: A Case Report and a Review of the Literature - Metin Şenol; Zehra Ünal Özdemir; İbrahim Tayfun Şahiner; Hakan Özdemir (Case Reports in Pediatrics)
Bezoar is defined as the accumulation of undigested foreign bodies or nutrients in the gastrointestinal tract. These foreign bodies can be hair (trichobezoar), fibers or seeds of vegetables and fruits (phytobezoar), or remnants of milk (lactobezoar) and stones (lithobezoar). Lithobezoar, the accumulation of stones in the digestive tract, is commonly seen in stomach. In this paper, a 7-year-old girl with colonic lithobezoar who presented with constipation, abdominal pain, and the history of pica was successfully treated by the extraction of the stones under general anesthesia.